Guidelines of the Italian Society of Videosurgery (SIVI) in Infancy for the minimally invasive treatment of Hypertrophic Pyloric Stenosis in neonates and infants - Salvatore Fabio Chiarenza; Cosimo Bleve; Maria Escolino; Ciro Esposito; Fabio Beretta; Maurizio Cheli; Maria Grazia Scuderi; Vincenzo Di Benedetto; Giovanni Casadio; Maurizio Marzaro; Marco Gambino; Andrea Conforti; et al. (PAGEPress Publications, 2020)
The most appropriate treatment for the infantile Hypertrophic Pyloric Stenosis (HPS) is still debated. The non-surgical conservative treatment with oral or intravenous administration of atropine does not enjoy a widespread appreciation for several factors (...)